2015
DOI: 10.2214/ajr.14.13235
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Kurtosis Imaging to Assess Response to Treatment in Hypervascular Hepatocellular Carcinoma

Abstract: DKI can be a new option for the assessment of posttherapeutic response in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 11 publications
4
78
1
Order By: Relevance
“…The use of DKI to probe the non‐Gaussian behavior of water diffusion in solid organs has been reported in several studies . In the present study, D app and ADC values decreased, whereas K app increased with increasing activity of CD.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The use of DKI to probe the non‐Gaussian behavior of water diffusion in solid organs has been reported in several studies . In the present study, D app and ADC values decreased, whereas K app increased with increasing activity of CD.…”
Section: Discussionsupporting
confidence: 55%
“…Although a maximum b‐value of 2000–2500 s/mm 2 was suggested in DKI of the brain, we set the highest b value at 2000 s/mm 2 because of lower signal‐to‐noise ratio (SNR) and faster signal decay of the transverse relaxation in the abdomen. Previous abdominal DKI studies have shown that the maximum b‐values of 800–2000 s/mm 2 were sufficient for estimating DKI parameter . Parallel imaging with short echo time of 80 msec was used in this study to improve the SNR.…”
Section: Discussionmentioning
confidence: 99%
“…The loose papillae, branching structure, and dense tiny cysts in BEOTs lead to a relatively easy diffusion of water molecules and therefore a higher ADC value . In addition, the studies showed that DKI was superior to standard DWI in assessment and early prediction of the response to treatment . Therefore, the DKI model may have potential advantages in the prediction or evaluation of the therapeutic effects of ovarian carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The DKI model can better describe the complexity of the tissue microstructure. Recently, several studies have shown the advantage of DKI in tumor detection, grading, and response to treatment . However, the utility of ovarian DKI has not been reported.…”
mentioning
confidence: 99%
“…Specifically, D* predicts lipiodol uptake[83]. DKI is reportedly a more reliable imaging biomarker than ADC[84]. …”
Section: Monitoring Of Therapymentioning
confidence: 99%